Genetic parameters of feed efficiency and its relationships with feed intake, daily gain and aminal size traits in Finnish blue fox (Alopex lagopus) - Kempe, Riitta; Strandén, Ismo; Koivula, Minna; Rekilä, Teppo; Koskinen, Nita; Mäntysaari, Esa (International Fur Animal Scientific Association (IFASA), 2008)
v 2008 ok BEL/BGE